دراسة تطور التحرير المصرفي في الدول النامية دراسة حالة الجزائر، تونس، المغرب و الاردن - سنوسي, قويدر; زناخي, فوزية (University of eloued جامعة الوادي, 2018)
تهدف هذه الورقة ل دراسة مسار التحرير المصرفي في الدول النامية، مع التركيز على الدول التالية الجزائر، تونس، المغرب و الأردن. و بعد تحليل البيانات و الجداول المحصل عليها من البنك العالمي و صندوق النقد العربي خلال الفترة 1990 إلى 2015، أظهرت النتائج أن الاردن حققت أعلى نسبة معروض نقدي تليها المغرب ثم تونس و الجزائر ،و هذا يعود الى مدى تطور النظام المصرفي في هذه الدول؛ أما نتائج مؤشر الائتمان الموجه للقطاع الخاص أن الجزائر في 1990 بلغت نسبتها من هذا المؤشر ما يفوق 55٪ و لكن سرعان ما انخفض خلال السنوات الموالية ،في حين أن المغرب و تونس و الأردن عرفت نمو مستمر، فقد حقق القطاع المالي في البلدان الأربعة توسع في الحجم والنشاط، خاصة الأردن، أما السياسة النقدية فقد اتسمت سنة 2013 بالاتجاه نحو التوسع و هو ما عكسه اتجاه معدل نمو السيولة المحلية على مستوى الدول، حيث نمت السيولة المحلية بمعدل 12.90٪ خلال سنة 2013 مقارنة بنحو 11.50٪ سنة 2012. وبالنسبة للجزائر، فإن مؤشرات التطور المالي تعكس قدرا من التحسن، الذي يبقى غير كاف قياسا إلى ما يشهده محيط نظامها المالي من تطورات وتحولات، الأمر الذي يستدعي مزيدا من العمل على تأهيل وتطوير هيكل وأداء هذا النظام. This paper aims to examine the banking liberalization path in developing countries, with a focus on the following countries Algeria, Tunisia, Morocco and Jordan. After analyzing the data obtained from the World Bank and the Arab Monetary Fund during the period 1990 to 2015, the results showed that Jordan had the highest proportion of cash supply, followed by Morocco, Tunisia and Algeria, this can be explained due to the evolution of the banking system in these countries; the orientated private sector credit index results to Algeria in 1990, which represented from this index exceeds 55%, but quickly declined during the following years, while Morocco, Tunisia, and Jordan knew continuous growth. The financial sector has achieved in the four countries expand in size and activity, especially Jordan, while monetary policy has been the year 2013 was characterized by a move towards expansion and is reflected in the direction of domestic liquidity growth at the country level rate, where domestic liquidity at a rate of 12.90% grew during the year 2013 compared to 11.50% in 2012. For Algeria, the development indicators financial reflect the degree of improvement, which remains inadequate compared to what witnessed in the vicinity of its financial system developments and transformations, which calls for more work on the rehabilitation and development of the structure and performance of this system.
مقال
Keywords: التحرير المصرفي، القطاع المصرفي، التسييل النقدي، الائتمان الخاص. liberation banking, the banking sector, the monetary liquefaction, private credit